Constructing a global education hub: the unlikely case of Manila. Issue 5 (3rd September 2018) - Ortiga, Yasmin Y.
ABSTRACT: This paper investigates the creation of an unlikely education hub in Manila, Philippines, where local institutions have seen a growing number of international students from Korea, India, and the Middle East. These students seek qualifications in professions where Filipino migrants are highly represented, either to gain an advantage within their home countries or as a steppingstone towards jobs elsewhere. Drawing from current debates on 'global cities', this paper discusses how different actors promote Manila as an ideal destination for students by using the country's unique position within the global market for migrant labor and its American colonial history. Here, Filipino school owners and state officials market Philippine universities as the best venue to train for jobs found anywhere in the world. Such strategies target less privileged students unable to access more prestigious universities. creating new forms of knowledge mobility in an increasingly segmented higher education market.